Progress in the development of stabilization strategies for nanocrystal preparations - Jingru Li; Zengming Wang; Hui Zhang; Jing Gao; Aiping Zheng (Taylor & Francis Group, 2021)
In recent years, nanocrystal technology has been extensively investigated. Due to the submicron particle size and unique physicochemical properties of nanocrystals, they overcome the problems of low drug solubility and poor bioavailability. Although the structures of nanocrystals are simple, the further development of these materials is hindered by their stability. Drug nanocrystals with particle sizes of 1∼1000 nm usually require the addition of stabilizers such as polymers or surfactants to enhance their stability. The stability of nanocrystal suspensions and the redispersibility of solid nanocrystal drugs are the key factors for the large-scale production of nanocrystal preparations. In this paper, the factors that affect the stability of drug nanocrystal preparations are discussed, and related methods for solving the stability problem are put forward.